2015
DOI: 10.1038/srep10268
|View full text |Cite|
|
Sign up to set email alerts
|

Digital Ecology: Coexistence and Domination among Interacting Networks

Abstract: The overwhelming success of Web 2.0, within which online social networks are key actors, has induced a paradigm shift in the nature of human interactions. The user-driven character of Web 2.0 services has allowed researchers to quantify large-scale social patterns for the first time. However, the mechanisms that determine the fate of networks at the system level are still poorly understood. For instance, the simultaneous existence of multiple digital services naturally raises questions concerning which conditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 35 publications
(45 reference statements)
1
37
0
Order By: Relevance
“…Here we are interested in how the topology of two networks and the correlations between layers can influence the distribution of the states among the nodes. Previously, it was shown that the relation between the layers in a real multiplex can be characterized by geometric correlations in hidden metric spaces underlying each layer of the system [34][35][36]. There are two kinds of correlations: popularity correlations, which are correlations between the degrees the nodes have in the two layers, and similarity correlations, which control the probability of the links overlapping between layers.…”
Section: Impact Of Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we are interested in how the topology of two networks and the correlations between layers can influence the distribution of the states among the nodes. Previously, it was shown that the relation between the layers in a real multiplex can be characterized by geometric correlations in hidden metric spaces underlying each layer of the system [34][35][36]. There are two kinds of correlations: popularity correlations, which are correlations between the degrees the nodes have in the two layers, and similarity correlations, which control the probability of the links overlapping between layers.…”
Section: Impact Of Correlationmentioning
confidence: 99%
“…This framework allows for a more realistic approach in the study of the interaction of individuals, which can communicate through different types of channel. Multiplex networks have been used to analyze public transportation systems [23,24], the spreading of awareness and infection [25,26], the dynamics of ecological populations [27,28], cultural dynamics [29] and the evolution of social networks [17,30].…”
Section: Introductionmentioning
confidence: 99%
“…where ρ a i denotes the fraction of active users in network i, λ is the total virality mentioned earlier, and k denotes 7 In the framework of [10], these equations are the result of taking the limit of ν → ∞, where ν describes the ratio between the rate at which the viral spreading and the influence of mass media occur. As shown in [10], taking this limit has no impact on the stability of the system.…”
Section: How a Social Bitcoin Could Sustain Digital Diversitymentioning
confidence: 99%
“…As shown in [10], taking this limit has no impact on the stability of the system. the mean degree of the network, i.e.…”
Section: How a Social Bitcoin Could Sustain Digital Diversitymentioning
confidence: 99%
“…As we explain in Sec. III C, the loss of diversity in the digital world can lead to a systematic and irreversible collapse of the digital ecosystem [10,11], akin to the loss of biodiversity in the physical ecosystem. Such a collapse can have dramatic consequences for the freedom of information and eventually for the freedom of society.…”
mentioning
confidence: 99%